AVRUPA BİRLİĞİ'NDE DEMOKRATİK MEŞRUİYET SORUNU - Sinem Akgül Açıkmeşe (Ankara Avrupa Çalışmaları Dergisi)
The European Union has long been criticized for its lack of democratic legitimation. Most of the scholarly work on the democratic deficit in the EU focuses on the institutional remedies such as empowering the European Parliament as the only directly democratically legitimized European decision-making Body, ensuring the transparency of the working methods of the EU institutions and simplifying the decision-making mechanism. The main aim of this article is to explore the origins of the democratic deficit in the EU, with a view to clar ^fy the impossibility of enhancing democratic legitimation in Europe through institutional means. Rather than seeing the institutional solutions as a panacea, the underlying assumption of this article is that the democratic character of the European political system depends on its capacity to achieve the European peoples' goals and solve their problems.